Infant Feeding in Relation to the Risk of Advanced Islet Autoimmunity and Type 1 Diabetes in Children With Increased Genetic Susceptibility: A Cohort Study. Issue 1 (1st June 2017) - Hakola, Leena; Takkinen, Hanna-Mari; Niinistö, Sari; Ahonen, Suvi; Nevalainen, Jaakko; Veijola, Riitta; Ilonen, Jorma; Toppari, Jorma; Knip, Mikael; Virtanen, Suvi M
Abstract: Breastfeeding, age at introduction of foods, and food diversity in infancy were studied for associations with advanced islet autoimmunity and type 1 diabetes. During 1996--2004, a total of 5, 915 newborns with human leukocyte antigen–conferred susceptibility to type 1 diabetes were enrolled in the prospective Finnish Type 1 Diabetes Prediction and Prevention Nutrition Study. Children were assessed at intervals of 3–12 months for the appearance of 4 types of islet autoantibodies and type 1 diabetes up to the age of 15 years. Survival models indicated the 3 variables of interest were not associated with advanced islet autoimmunity or type 1 diabetes in the cohort. Early introduction of solid foods was associated with increased risk of advanced islet autoimmunity in children up to age 3 years (for <3 months vs. >4 months, hazard ratio = 2.33, 95% confidence interval: 1.39, 3.91; for 3–4 months vs. >4 months, hazard ratio = 2.18; 95% confidence interval: 1.38, 3.47) but not in longer follow-up ( P for interaction = 0.046). Similar results were observed for age at introduction of roots, cereals, egg, and meat relative to risk of advanced islet autoimmunity. No consistent, long-term associations between infant feeding and advanced islet autoimmunity or type 1 diabetes were observed.